Discrete Geometry, Combinatorics and Graph Theory [electronic resource] : 7th China-Japan Conference, CJCDGCGT 2005, Tianjin, China, November 18-20, 2005, and Xi'an, China, November 22-24, 2005, Revised Selected Papers - CJCDGCGT 2005 (2005 : Tianjin, China and Xi'an, Shaanxi Sheng, China); Akiyama, Jin.; SpringerLink (Online service) (Berlin Heidelberg : Springer-Verlag GmbH., 2007)
PSZJBL